Competencias del trabajador social y la implementación de estrategias de bioseguridad frente a la pandemia COVID-19 en la Parroquia Tendales - Ochoa Morocho, Dennis Joel; Soria Jativa, Katherine Abigaíl (Machala, 2021)
During the COVID-19 pandemic, the family economy was affected by the temporary closure of several public and private companies which had been generating employment and in turn the suspension of commercial activities which represented a risk for the population due to the lack of biosecurity measures in these times of crisis; For this reason, during the commercial paralysis caused by this pandemic, some families engaged in other types of activities such as survival strategies that did not represent a risk of contagion for families and the community. The present work of systematization of experiences, aims to analyze the social worker competencies associated with the implementation of biosafety strategies in the face of this pandemic in Tendales Parish, El Guabo canton. This health problem is affecting the inhabitants who are not aware of the risks of contracting in this pandemic; That is why the support of the Parish GAD of Tendales is important so that the biosafety protocols are properly applied. The research that was used is of a qualitative approach with the application of qualitative techniques such as observation, interviews and focus group in order to collect field data by reviewing scientific articles from indexed journals that provide the necessary information to carry out this research work that explains the reality that the families of the Tendales parish experience in the face of this pandemic, through the construction of a theoretical foundation and proposal that allow the inclusion of the population, while the process of isolation due to this pandemic is carried out. The competences carried out by the social worker during the pandemic are diverse, highlighting the execution of social investigations, in order to know the quality of life of the families, the understanding of the risk of contagion and the adaptability of the community. As social workers participating in this research aimed at the inhabitants of the Tendales parish, the implementation of an inclusive biosecurity strategy is incorporated, referring to the creation of an intervention plan in the fight against this pandemic, applying professional skills and developing functions as information, guidance, prevention and promotion to support families, thus giving a prompt response to the increase in the rate of infected since currently, due to the pandemic, many families have suffered the loss of their loved ones, but all this is given to cause of the lack of knowledge about the necessary biosecurity measures to maintain the health of the population since the quality of life has worsened during this pandemic showing fear, anxiety, worry, stress, uncertainty, sadness, nostalgia and vulnerability. For this reason, apart from implementing biosafety measures, an awareness campaign on preventive measures for the pandemic has also been promoted for the population, carrying the message of becoming aware of the contagion in the community context and through this to be able to obtain a better reception of the preventive measures that will protect the lives of the inhabitants of the Tendales parish.
Durante la pandemia COVID-19, la economía familiar se vio afectada por el cierre temporal de varias empresas públicas y privadas las cuales habían sido generadoras de empleo y a su vez la suspensión de actividades comerciales las cuales representaban un riesgo para la población por la carencia de medidas de bioseguridad en estos tiempos de crisis; por eso durante la parálisis comercial provocada por esta pandemia, algunas familias se dedicaron a otro tipo de actividades como estrategias de supervivencia que no representaran un riesgo de contagio para las familias y la comunidad. El presente trabajo de sistematización de experiencias, tiene como objetivo analizar las competencias del trabajador social asociadas a la implementación de estrategias de bioseguridad frente a esta pandemia en la Parroquia Tendales, del cantón El Guabo. Esta problemática de salud está afectando a las y los habitantes quienes no son conscientes de los riesgos que hay de contraer en esta pandemia; por eso es importante el apoyo del GAD parroquial de Tendales para que se apliquen debidamente los protocolos de bioseguridad. La investigación que se utilizó es de enfoque cualitativo con la aplicación de las técnicas cualitativas tales como observación, entrevistas y grupo focal para así recopilar datos de campo revisando artículos científicos de revistas indexadas que proporcionen la información necesaria para la realización de este trabajo de investigación que explica la realidad que viven las familias de la parroquia Tendales frente a esta pandemia, a través de la construcción de una fundamentación teórica y propuesta que permitan la inclusión de la población, mientras se cumpla el proceso de aislamiento por esta pandemia. Las competencias que realiza el trabajador social durante la pandemia son diversas destacando la ejecución de investigaciones sociales, con la finalidad de conocer la calidad de vida de las familias, el entendimiento del riesgo de contagio y la adaptabilidad de la comunidad. Como trabajadores sociales participantes de esta investigación dirigida a las y los habitantes de la parroquia Tendales, se incorpora la implementación de una estrategia de bioseguridad inclusiva referida a la creación de un plan de intervención en la lucha contra esta pandemia, aplicando competencias profesionales y desarrollando funciones como información, orientación, prevención y promoción para apoyar a las familias dando así una pronta respuesta al incremento de la tasa de infectados puesto que actualmente a causa de la pandemia muchas familias han sufrido la pérdida de sus seres queridos, pero todo esto se da a causa de la falta de conocimiento sobre las medidas de bioseguridad necesarias, para mantener la salud de la población ya que la calidad de vida ha empeorado durante esta pandemia mostrando miedo, ansiedad, preocupación, estrés, incertidumbre, tristeza, nostalgia y vulnerabilidad. Es por esto que aparte de implementar las medidas de bioseguridad también se ha promovido una campaña de sensibilización sobre las medidas preventivas ante la pandemia para la población, llevando el mensaje de tomar conciencia del contagio en el contexto comunitario y mediante esto poder obtener un mejor acogimiento de las medidas preventivas qué pondrán proteger la vida de las y los habitantes de la parroquia Tendales.
Keywords: COMPETENCIA; TRABAJO SOCIAL; PANDEMIA; COMUNIDAD